1993
DOI: 10.1007/bf00315398
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma and urinary 11-dehydrothromboxane B2 in healthy subjects produced by oral CS-518, a novel thromboxane synthase inhibitor

Abstract: When 50 mg CS-518, a novel thromboxane (TX) A2 synthase inhibitor, was orally administered to healthy male volunteers, the plasma concentration of CS-518 peaked after 0.5 h and then decreased with a half-life of 0.44 h. There was no significant change in the plasma concentration of circulating TXB2, whereas that of circulating 11-dehydrothromboxane B2 (11-dhTXB2), an enzymatic metabolite of TXB2, was significantly decreased from 0.5 h to 24 h after administration; the maximal decrease to about 25% of the pre-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A genetically tailored antiplatelet therapy within the study population is needed as previous studies have found a high prevalence of clopidogrel resistance in Asian populations [13,14] . In recent years, the most common CYP2C19*2, *3 mutation sites in the human cytochrome P450 allele have attracted much attention [15][16][17][18] . Aspirin is widely used in secondary prevention of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A genetically tailored antiplatelet therapy within the study population is needed as previous studies have found a high prevalence of clopidogrel resistance in Asian populations [13,14] . In recent years, the most common CYP2C19*2, *3 mutation sites in the human cytochrome P450 allele have attracted much attention [15][16][17][18] . Aspirin is widely used in secondary prevention of stroke.…”
Section: Introductionmentioning
confidence: 99%